Improving the Psychological Welfare of the Elderly Through Islamic Religious Education Services at the Elderly Posyandu in Perigi Village, Silat Hilir District, Kapuas Hulu Regency - Khair, Fathul (Journal of English Language and Education, 2026)
Aging is an inevitable natural process, an inseparable part of life's journey. As they age, elderly individuals are often faced with various challenges, both physically, biologically, psychologically, and socially. This research focuses on the phenomenon of declining psychological conditions of the elderly, which is often characterized by feelings of loneliness, helplessness, and loss of meaning in life. This feeling arises due to social limitations and the change in their role in the family and society. This study aims to analyze the role of Islamic religious education services in improving the psychological welfare of the elderly in the Elderly Posyandu in Perigi Village, Silat Hilir District. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation on Posyandu administrators, religious advisors, and the elderly. The results of the study show that Islamic religious education services, which include activities such as routine recitation, worship guidance, joint dhikr, as well as moral and spiritual development, have a significant contribution to improving psychological well-being in the elderly. The elderly become calmer, more patient, optimistic, and have a higher sense of gratitude and meaning in life. In addition, religious activities also strengthen social relations between the residents of the orphanage and create a harmonious and affectionate environment. This study concludes that Islamic religious education plays an important role as a spiritual and social medium in building mental, emotional, and spiritual balance in the elderly.